Tumour necrosis factor α signalling through activation of Kupffer cells plays an essential role in liver fibrosis of non-alcoholic steatohepatitis in mice. Issue 3 (20th September 2005) - Tomita, K; Tamiya, G; Ando, S; Ohsumi, K; Chiyo, T; Mizutani, A; Kitamura, N; Toda, K; Kaneko, T; Horie, Y; Han, J-Y; Kato, S; et al.
Abstract : Background: While tumour necrosis factor α (TNF-α) appears to be associated with the development of non-alcoholic steatohepatitis (NASH), its precise role in the pathogenesis of NASH is not well understood. Methods: Male mice deficient in both TNF receptors 1 (TNFR1) and 2 (TNFR2) (TNFRDKO mice) and wild-type mice were fed a methionine and choline deficient (MCD) diet or a control diet for eight weeks, maintaining isoenergetic intake. Results: MCD dietary feeding of TNFRDKO mice for eight weeks resulted in attenuated liver steatosis and fibrosis compared with control wild-type mice. In the liver, the number of activated hepatic Kupffer cells recruited was significantly decreased in TNFRDKO mice after MCD dietary feeding. In addition, hepatic induction of TNF-α, vascular cell adhesion molecule 1, and intracellular adhesion molecule 1 was significantly suppressed in TNFRDKO mice. While in control animals MCD dietary feeding dramatically increased mRNA expression of tissue inhibitor of metalloproteinase 1 (TIMP-1) in both whole liver and hepatic stellate cells, concomitant with enhanced activation of hepatic stellate cells, both factors were significantly lower in TNFRDKO mice. In primary cultures, TNF-α administration enhanced TIMP-1 mRNA expression in activated hepatic stellate cells and suppressed apoptotic induction in activated hepatic stellate cells. Inhibition of TNF induced TIMP-1 upregulation by TIMP-1 specific siRNA reversed the apoptotic suppression seen in hepatic stellate cells. Conclusions: Enhancement of the TNF-α/TNFR mediated signalling pathway via activation of Kupffer cells in an autocrine or paracrine manner may be critically involved in the pathogenesis of liver fibrosis in this NASH animal model.